2001
DOI: 10.1108/eum0000000005789
|View full text |Cite
|
Sign up to set email alerts
|

Robust estimation of hedonic models of price and income for investment property

Abstract: Real estate market data often contain outliers in the observations. Since outliers have a large influence on least squares estimates, robust regression methods have been recommended for this situation. Compares the performance of least squares and least median of squares, a robust method, in the estimation of price/income relationships for apartment buildings. Multiplicative models with multiplicative errors are estimated by means of natural log transformations. The study confirms the importance of employing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…Fewer variations in structural and locational attributes of the residential units could permit a better understanding of environmental effects on housing price. The judicious selection of sample areas and commonality of the explanatory variables also help to improve data quality (Garrod and Willis, 1999;Luttik, 2000;Janssen et al, 2001;Haab and McConnell, 2002;Malpezzi, 2003).…”
Section: Sample Areas and Datamentioning
confidence: 99%
“…Fewer variations in structural and locational attributes of the residential units could permit a better understanding of environmental effects on housing price. The judicious selection of sample areas and commonality of the explanatory variables also help to improve data quality (Garrod and Willis, 1999;Luttik, 2000;Janssen et al, 2001;Haab and McConnell, 2002;Malpezzi, 2003).…”
Section: Sample Areas and Datamentioning
confidence: 99%
“…They emphasize that quality adjustment of cap rates is important, since they find wide disparities between their constant-quality cap rate series and simple averages. Janssen et al (2001) also analyze the Stockholm market. Based on 302 predominantly residential transactions from 1992 to 1994, they find property type, age, and dummy variables for four areas of the city to be significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that the cap rates of apartments are lower than those of commercial properties, those of offices are lower than those of retail properties, and those of better regions are lower than those of depressed regions. Janssen et al (2001) analyzed data from 351 income properties in downtown Stockholm between 1992 and 1994, as provided by the Swedish Land Data Bank System, and established a hedonic equation of rent and price to estimate cap rates of the transactions, and then used OLS (ordinary least squares) and RLMS (reweighted least median squares) to estimate and compare whether the implicit prices of the properties differed between dissimilar estimation methods. The empirical results showed that the greater the age of the apartment, the higher the cap rate, because the requirement of substantial maintenance costs and a shorter service life decrease the property value.…”
Section: Literature Reviewmentioning
confidence: 99%